Paradox of change in women’s capabilities: Case of two villages in Bangladesh - Huq, Lopita (BRAC Institute of Governance and Development (BIGD), 2022)
The paper seeks to understand why women’s capabilities and outcomes signiﬁcantly vary in two apparently similar contexts characterized by prosperity, international migration and religiosity. By analyzing the data from two purposively selected villages of Sylhet and Chittagong, it attempts to understand the factors that drive or resist changes in social behaviour. This paper ﬁnds that both physical and ideational connectivity and interaction with institutions can play a big role. It further points to a need to examine the norms and values such as patriarchal control, social cohesion and religiosity that reﬂect the wider context and shape women’s agency and outcomes.